Socioeconomic, Laboratory and Associated Factors in Patients Suffering From Acute Appendicitis - Ahmad Arsalan Tahir, Anwar Ali, Mohammad Usman, Nasir Bakhtiar, Ibrahim, Asad Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute appendicitis (AA) is the most common clinical condition worldwide. In Pakistan, about 400,000 appendectomies are routinely carried out in surgical departments yearly. This study aims to find the latest and updated information regarding the diagnostic accuracy of CRP levels in AA. This will help surgeons make timely decisions, thus reducing the morbidity and mortality associated with complicated appendicitis. Methods: This descriptive cross-sectional study was performed at KTH Peshawar from February to august 2018. It was designed to analyze C-reactive protein levels among acute appendicitis patients using positive and negative predictive values. Histopathologically confirmed appendicitis patients were included. Results: In the current study, 216 patients suffering from Acute appendicitis were studied observed. The symptoms duration was < 2days in 75% patients while >2 days symptoms were found in 25% population. Majority patients were poor (46%), followed by middle class (42%), and rich (12%). Obesity was only observed in 22% patients suffering from AA. Diabetes and hypertension was observed in 18% and 15% patients respectively. Diagnostic accuracy of acute appendicitis was also calculated between CRP and Histopathology findings based on age, diabetes mellitus, gender, hypertension, obesity, and period of symptoms. Conclusion: Our study concludes that the acute appendicitis symptoms appeared in less than two days. Acute appendicitis predominantly found in poor and middle class patients. Acute appendicitis should be diagnosed based mostly on its clinical symptoms. Despite the fact that CRP is a particularly helpful marker in the clinical diagnosis of acute appendicitis, general surgeons must apply their clinical judgement. The function of CRP in acute appendicitis should be examined in future research with a bigger sample size. Keywords: C-reactive protein level, Socioeconomical factors, Acute Appendicitis, Diagnostic accuracy, Histopathological.